Effect of integrated nutrient management on zinc fractions and rice yield - Singh, Navdeep; Gill, RS; Dheri, GS (ORYZA-An International Journal of Rice, 2019)
Integrated nutrient management (INM) effects chemical transformation of nutrients in soil and plant uptake. This study present the long-term (30 years) effects of integrated nutrient management on zinc (Zn) fractions and rice yield. The treatments include ten combinations of nitrogen, phosphorous and potassium applied through mineral fertilizers and substituted through farmyard manure (FYM), green manure (GM) and wheat cut straw (WCS).The distribution of Zn into exchangeable (EXCH), carbonate bound (CARB), organic matter bound (OM), manganese oxides bound (MnOX), amorphous iron oxide bound (AFeOX) and crystalline iron oxide bound (CFeOX) was determined. The effect of long-term use of mineral fertilizers on EXCH-Zn was not significantas compared to control, however, EXCH-Zn increased significantly in INM treatments compared to both control and mineral fertilizer in surface soil (0-15 cm). Similarly, CARB-Zn and OM-Zn was significantly higher in INMas compared to control and mineral fertilizer treatments. The distribution of Zn in MnOX, AFeOX and CFeOX fractions was not distinctly affected with long-term fertilizations. In general, concentration of Zn fractions was lower in subsurface soils (15-30 cm) as compared to surface soils. The grain yield of rice increased in order control< mineral fertilizers